The double bind as world image in La Nave de los Locos by Cristian Peri Rossi - Cisternas Ampuero, Cristián; Valenzuela Tapia, Patricia (Revista Chilena de Literatura, 2017)
This article deals with the concept of “double bind”, as applied to La nave de los locos (1984), a Latin American contemporary novel by Cristina Peri Rossi. I argue that the psychiatric notion of “double bind” helps to understand the image of a world of anguish and dislocation that surrounds the characters. Moreover, this article proposes a possibility of escape from this existential condition.